The potential of integration of Macedonian functioning market in the European Union - Petrevska, Biljana (My University, 2018)
The fact that Macedonia aspires to become a member state of the European Union, it will have to align its market with the EU. Therefore the main objective of this paper is to analyze the actual process of harmonization and convergence of functioning market in Macedonia in light of access to the European Union. The first part of this paper presents an introduction to the framework, while the second part focuses on the existence of a functioning market economy in Macedonia. Finally, in the third part of this paper, we are giving our basic conclusions.
Keywords: market, economy, functioning market economy, European Union